2018
DOI: 10.1364/ol.43.000755
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency all-fiber cylindrical vector beam laser using a long-period fiber grating

Abstract: We demonstrate a novel all-fiber laser generating cylindrical vector beams with high slope efficiency and low threshold by introducing a long-period fiber grating into the laser cavity. Highly efficient mode conversion is realized by an LPFG at ∼1548  nm. Mode selection and spectrum filtering are achieved in combination with a two-mode fiber Bragg grating (TM-FBG). The fiber laser operates at a single wavelength of 1547.95 nm with a 30 dB linewidth of less than 0.18 nm and a side-mode suppression ratio (SMSR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Chen et al. demonstrated a fiber laser generating cylindrical vector beam efficiently in 1.5 µm band using long period grating . In a previous work of our group, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al. demonstrated a fiber laser generating cylindrical vector beam efficiently in 1.5 µm band using long period grating . In a previous work of our group, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber lasers with pure high-order-mode (HOM) output have been intensively studied in recent years owing to their unique polarization, amplitude and phase characteristics. Generally, there are several commonly used approaches to realize HOM operation, including adopting spatial light modulators [1], [2], employing long period gratings [3], [4], introducing adaptive control [5]- [7], using few-mode fiber Bragg gratings (FBGs) [8]- [10] and taking advantage of mode selective couplers [11], [12]. Currently, exploration on HOM fiber lasers has focused on power scaling [13], nonlinear conversion [4], [14], vector beam generation [15], etc.…”
Section: Introductionmentioning
confidence: 99%
“…After that, Xiao et al reported on soliton molecules in multimode fiber lasers by adjusting the waveplates inside the cavity, and observed transition states of different operations in different pump powers [33]. As a typical few-mode fiber, two-mode fiber (TMF) can support the propagation of LP 01 and LP 11 modes, and mode-selective couplers, few-mode fiber gratings, as well as lateral offset-spliced fibers have been broadly used to generate cylindrical vector beams [34]- [36] and vortex beams [37]- [39]. Dong et al reported the transverse modes switchable mode-locked fiber laser by using a two-mode fiber Bragg grating for transverse-mode selection [40].…”
Section: Introductionmentioning
confidence: 99%